2022
DOI: 10.3329/ijarit.v12i1.61050
|View full text |Cite
|
Sign up to set email alerts
|

Financial profitability analysis of dairy milk production in some selected areas of Bangladesh

Abstract: The study analyzed profitability and productivity of dairy milk production from a survey of 70 respondents (farmers and market actors) in Dhaka region. Responsible factors that affect dairy milk production were identified using the Cobb-Douglas production function. The findings unveil that significant coefficients of variables exhibit positive impact on the dairy milk production. It is possible for dairy farmers to enjoy sufficient profits from milk production since earned gross return and net return were Tk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(18 reference statements)
0
3
1
Order By: Relevance
“…Md. Ariful Alam et al (2022) reported that the production of milk per cow per day is 12.5 liters which is more than that of the present study. The reason is that Md.…”
Section: Profitability Analysis For Cattle Fatteningcontrasting
confidence: 63%
See 2 more Smart Citations
“…Md. Ariful Alam et al (2022) reported that the production of milk per cow per day is 12.5 liters which is more than that of the present study. The reason is that Md.…”
Section: Profitability Analysis For Cattle Fatteningcontrasting
confidence: 63%
“…92.954 thousand BDT per cow per year. This implies that dairy milk production was a profitable enterprise for small and medium dairy farmers and the result is nearer to line with the findings of Alam et al (2022). The average fixed cost per cow per year was .822 thousand BDT which includes the cost of house building and maintenance costs for cattle farming.…”
Section: Profitability Analysis For Cattle Fatteningmentioning
confidence: 70%
See 1 more Smart Citation
“…The country enacted the Right to Information Act in 2009 which provided people with a foundation to enjoy freedom of information (Hoque, 2018a). The country's robust economic growth created positive impacts in all sectors, including agriculture, poverty reduction, energy, technology, governance, and so forth (Adnan et al, 2021a(Adnan et al, , 2021bHoque, 2014aHoque, , 2016Hoque, , 2018bHoque, , 2020aHoque, , 2020bHoque, , 2021aHoque, , 2021bHoque & Tama, 2020, 2021Sarker et al, 2020;Tama et al, 2015Tama et al, , 2018Tama et al, , 2021. However, the situation has changed in the last decade, especially with the massive growth of social media (such as Facebook) and online news portals.…”
Section: Introductionmentioning
confidence: 99%